Biphasic papillary renal cell carcinoma is a rare morphological variant with frequent multifocality: a study of 28 cases - Trpkov, Kiril; Athanazio, Daniel; Magi-Galluzzi, Cristina; Yilmaz, Helene; Clouston, David; Agaimy, Abbas; Williamson, Sean R; Brimo, Fadi; Lopez, Jose I; Ulamec, Monika; Rioux-Leclercq, Nathalie; Kassem, Maysoun; et al. (Histopathology, 2018)
AIMS: To further characterise biphasic squamoid renal cell carcinoma (RCC), a recently proposed variant of papillary RCC. METHODS AND RESULTS: We identified 28 tumours from multiple institutions. They typically showed two cell populations-larger cells with eosinophilic cytoplasm and higher-grade nuclei, surrounded by smaller, amphophilic cells with scanty cytoplasm. The dual morphology was variable (median 72.5% of tumour, range 5-100%); emperipolesis was found in all cases. The male/female ratio was 2:1, and the median age was 55 years (range 39-86 years). The median tumour size was 20 mm (range 9-65 mm). Pathological stage pT1a was found in 21 cases, pT1b in three, and pT3a and pT3b in one each (two not available). Multifocality was found in 32%: multifocal biphasic RCC in one case, biphasic + papillary RCC in two cases, biphasic + clear cell RCC in three cases, biphasic + low-grade urothelial carcinoma of the renal pelvis in one case, and biphasic + Birt-Hogg-Dubé syndrome in one case. Positive immunostains included: PAX8, cytokeratin (CK) 7, α-methylacyl-CoA racemase, epithelial membrane antigen, and vimentin. Cyclin D1 was expressed only in the larger cells. The Ki67 index was higher in the larger cells (median 5% versus ≤1%). Negative stains included: carbonic anhydrase 9, CD117, GATA-3, WT1, CK5/6, and CK20; CD10 and 34βE12 were variably expressed. Gains of chromosomes 7 and 17 were found in two evaluated cases. Follow-up was available for 23 patients (median 24 months, range 1-244 months): 19 were alive without disease, one was alive with recurrence, and one had died of disease (two had died of other causes). CONCLUSIONS: Biphasic papillary RCC is a rare variant of papillary RCC, and is often multifocal.
Keywords: nádory ledvin; Humans; lidé středního věku; Biomarkers, Tumor; Female; Aged; biphasic; dospělí; senioři; lidé; papillary renal cell carcinoma; nádorové biomarkery; Adult; ženské pohlaví; Male; Middle Aged; alveolar; Aged, 80 and over; squamoid; immunohistochemistry; karcinom z renálních buněk; kidney; solid variant of papillary renal cell carcinoma; senioři nad 80 let; Carcinoma, Renal Cell; mužské pohlaví; Kidney Neoplasms